Tolerating climate change: a study on the influence of thermal history on thermal tolerance of Galaxias zebratus in rivers of the Cape Peninsula, South Africa - Olsen, Toni (Department of Environmental and Geographical Science, 2019)
Global climate change models predict a reduction in rainfall and rise in air temperature for the Cape Peninsula of South Africa’s Cape Floristic Region (CFR). The CFR is a biodiversity hotspot renowned for its high level of floral endemism, but the high level of endemism also applies to the region’s freshwater fish assemblage. Whereas the current threats to endemic freshwater fish include habitat modification, water abstraction, pollution and impacts of non-native species, climate change is predicted to further exacerbate negative impacts on fish communities. The endemic CFR fish species, Cape Galaxias, Galaxias zebratus Castelnau, 1861, is widespread throughout the region, and occurs in both non-perennial and perennial rivers, and wetlands. The species is thought to be a relict group of ancient species originating from the break up of Gondwanaland 180 – 135 million years ago. Endemic CFR freshwater fish, like G. zebratus, may be sensitive to the thermal regime of their environment and may thus be influenced by climate warming. The most commonly used experimental approach for determining the effect of elevated temperature on freshwater biota is the Critical Thermal Method (CTM). The CTM determines the upper thermal tolerance limit or critical thermal maximum (CTmax) of a species. Thermal history is the range of temperatures experienced by an organism in its natural habitat over time and this may be an important factor determining the thermal tolerance of species. The aim of this study was to evaluate the influence of thermal history, reflecting a stream’s thermal profile, on upper thermal tolerance limits of G. zebratus. We hypothesised that G. zebratus from warmer sites would have a higher CTmax than individuals at cooler sites. To examine the influence thermal history has on the thermal tolerance of G. zebratus, hourly water temperature data were collected and the CTmax values were determined for fish (n=30 per site) from 10 different sites in rivers of the Cape Peninsula. The CTmax values from all sites for the November-December experimental period ranged from 30.00°C to 32.45°C. CTmax values for all sites from the JanuaryFebruary experimental period ranged from 31.29°C to 33.42°C. Upper thermal tolerance limits of G. zebratus increased from the November-December experiments to the January-February experiments. Regression analyses show that G. zebratus upper thermal tolerance limits are significantly influenced by its thermal history as characterised by the seven day moving average of daily mean (Mean_7) two weeks preceding the experiments, implying that changes to the thermal regime will influence the thermal tolerance of G. zebratus. The resultant regression equation allows G. zebratus CTmax to be predicted by thermal history based on Mean_7, providing valuable information to set thermal limits of G. zebratus and guide future research. This is the first study on the thermal ecology of G. zebratus in the CFR and in Africa. The data not only enhance understanding of the thermal ecology of the species, but also further our understanding of their potential vulnerability to climate change.